2008
DOI: 10.1002/ps.1622
|View full text |Cite
|
Sign up to set email alerts
|

Actions of quinolizidine alkaloids on Periplaneta americana nicotinic acetylcholine receptors

Abstract: Three of the four natural alkaloids tested possess structural moieties that are necessary for interaction with P. americana nAChRs. Aloperine, which possesses a unique structure and showed a distinctive dose-response curve, was found to act as an antagonist. Appropriate modifications of these alkaloids might result in novel insecticidal nAChR ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Based on the results of current and previous studies, we can hypothesize that the enzymatic defence of B. tabaci is activated by the assault of either matrine or L. muscarium and that the combination of these two agents can overcome this defence strategy through a strong synergistic effect. The chemical basis of this strong synergistic effect is possibly related to the disturbance of the acetylcholine balance and changes in AchE activities of the whitefly as both matrine and L. muscarium can target insect acetylcholine (Ach) receptors which in turn effects AchE production2440. Therefore, our results have revealed the complex biochemical processes involved in the synergistic action of matrine and L. muscarium against B. tabaci .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Based on the results of current and previous studies, we can hypothesize that the enzymatic defence of B. tabaci is activated by the assault of either matrine or L. muscarium and that the combination of these two agents can overcome this defence strategy through a strong synergistic effect. The chemical basis of this strong synergistic effect is possibly related to the disturbance of the acetylcholine balance and changes in AchE activities of the whitefly as both matrine and L. muscarium can target insect acetylcholine (Ach) receptors which in turn effects AchE production2440. Therefore, our results have revealed the complex biochemical processes involved in the synergistic action of matrine and L. muscarium against B. tabaci .…”
Section: Discussionmentioning
confidence: 75%
“…The decrease in AchE activities can be related to the mode of action of both agents. Matrine, an alkaloid extracted from S. flavescens is known to target insect acetylcholine (Ach) receptors which in turn effects AchE production40. Luo et al 34.…”
Section: Discussionmentioning
confidence: 99%
“…Sophora is an ancient Chinese herb (Akdeniz & Ozmen 2011). It was found that oxymatrine is produced oxidation of matrine and it acts on nicotinic acetylcholine receptor in American cockroaches, Periplaneta americana (Liu et al 2008). This insecticide has no cytotoxic and genotoxic effects on plants so it can be proposed as a safe biopesticide tool (Akdeniz & Ozmen 2011).…”
Section: Biology and Problems Concerning Frankliniella Occidentalismentioning
confidence: 99%
“…고삼 추출물의 병해충 방제 기능 성분으로는 matrine, oxymatrine 같은 alkaloid 계열성분 (Liu et al, 2008)과 polyphenol계열의 sophoraflavanone G (Cha et al, 2007), saponin계열의 soyasaponin I (Taylor et al, 2007 에 의한 분해 촉매작용이 주요한 요인으로 고려되었다. 또한, 노출 후반기의 분해율이 급격히 감소하는 것은 고삼 추출물 등 처리된 유기물이 토양 표면에 견고한 피막을 형성하기 때 문인 것으로 판단된다 (Fig.…”
unclassified